A study on Effects of pH, Adsorbent Dosage, Time, Initial Concentration and Adsorption Isotherm Study for the Removal of Hexavalent Chromium (Cr (VI)) from Wastewater by Magnetite Nanoparticles. (2016) - Padmavathy, K.S.; Madhu, G.; Haseena, P.V.
Abstract: Magnetite nanoparticles synthesized in the laboratory were used for the removal of Hexavalent chromium (Cr (VI)) from synthetically prepared wastewater. The synthesized particles were characterized using scanning electron microscopy equipped with energy dispersive X-Ray spectroscopy, X ray diffraction and thermogravimetric analyzer. Batch adsorption studies were conducted to study the effects of pH, magnetite dosage, time and initial concentration on Cr (VI) removal. Adsorption isotherm study was also conducted. Optimum pH for the present work was 3.0 and all the other studies were done at this pH. The adsorption followed Freundlich isotherm model.UV-VIS spectrophotometer was used to measure the concentration of Hexavalent chromium in water.